KNOWLEDGE, ATTITUDES AND PRACTICES REGARDING HUMAN IMMUNODEFICIENCY VIRUS/ACQUIRED IMMUNE DEFICIENCY SYNDROME AND SEXUALLY TRANSMITTED INFECTIONS AMONG HEALTH CARE PROVIDERS IN LAHORE, PAKISTAN - Khan, Mohsin Saeed; Unemo, Magnus; Zaman, Shakila; Lundborg, Cecilia Stålsby (Journal of Ayub Medical College Abbottabad, 2009)
Background: Human Immunodeficiency Virus (HIV) infection is a global problem of extraordinary dimensions and has so far resulted in nearly 25 million deaths worldwide. Health care providers (HCPs) are considered to play a pivotal role in the provision of preventive and curative services to individuals suffering from HIV/AIDS and sexually transmitted infections. Pakistan, which was previously categorised as having a low-prevalence, high-risk HIV epidemic, is now facing a concentrated HIV epidemic among its most at-risk populations such as injecting drug users. The objective of this study was to assess the knowledge, attitudes and reported practices relating to HIV/AIDS and STIs among private and public sector health care providers providing clinical services in areas where women sell sex. Methods: This was an exploratory quantitative study, where a structured questionnaire was administered in face-to-face interviews with 200 HCPs from the public and private sectors. Knowledge about AIDS and correct diagnosis of STIs were defined as according to the national guidelines of NACP. Pearson's chi-square analysis was performed to test associations between predictors and level of knowledge of STIs in each group separately. Multivariate logistic regression analysis was employed to indicate predicting factors for correct management of STIs. Results: Forty-five percent of the HCPs had correct knowledge about the transmission and prevention of HIV, whereas 21% had seen a patient with advanced HIV infection, only two HCPs had been trained to manage such cases and 82% were not aware of syndromic management of STIs. Only 10% could cite the '˜correct treatment' of gonorrhoea, syphilis and vaginal discharge. The odds of having the '˜correct knowledge' of diagnosing gonorrhoea and syphilis were 2.1 (CI 95%, 1.2-3.8) if the HCP was a female medical doctor working in public sector. Conclusion: Further intensive training is needed to improve the ability of relevant HCPs to correctly diagnose and effectively treat patients infected with HIV and STIs. Keywords: HIV/AIDS, Sexually transmitted infections (STI), health care providers (HCP), knowledge attitudes and practices (KAP), Pakistan